MY SAY: Embracing commercial Islam - Abd Razak, Dzulkifli (2009)
It was not too long ago that Islam was "reintroduced" to the world in a very brutal manner — the tragedy of Sept 11, 2001. It was then that the "crusade" (to use the word of the then US President George W Bush) against Islam was launched on the back of the "war on terrorism". This summarily led to the fall of Baghdad, the invasion of Afghanistan, the profiling of practically all Muslims and anything that was Islamic.